COVID-19: Estimating impact on the economy and poverty in Pakistan: Using SAM Multiplier Model - Moeen, Muhammad Saad; Haider, Zeeshan; Shikoh, Sania Haider; Rizwan, Noormah; Davies, Stephen; Rana, Abdul Wajid (International Food Policy Research Institute, 2020)
Social Accounting Matrix (SAM) multiplier analysis has been employed to assess the impacts of COVID-19 on various macroeconomic variables including Gross Domestic Product (GDP), employment, and poverty in Pakistan. SAM multiplier models are well-suited to estimate the direct and indirect effects of unanticipated demand-side shocks and short-term fluctuations on various sectors and agents in the economy, such as those caused by the COVID19 pandemic. The results show that Pakistan’s GDP declined by 26.4 percent from mid-March to the end of June 2020 (14 weeks) compared to a non-COVID scenario. Services were hit the hardest, registering losses of 17.6 percent, followed by industry with losses of 6.7 percent. Agriculture turned out to be resilient and remained relatively unhurt, falling by 2.1 percent. All households witnessed a reduction in incomes, but higher-income quartiles appeared to have lost more than lower-income ones. Our approach for economic impact with mitigation measures is to assess the effectiveness of Emergency Response Packages (ERP) by altering the remittances to levels that reflect the magnitude of the support from the government. The total government expenditures were directed towards different kinds of households of PKR 318.6 billion (USD 2.12 billion). This led to a reduction of about USD 3.1 billion in GDP losses, which, compared to the amount spent implied a multiplier of 1.4 in GDP per PKR spent. The national poverty rate soared to 43 percent and 38.7 percent in April and May respectively. The Government’s cash transfers program proved highly effective and led to 11 percent reduction in poverty rate during the pandemic. The recovery scenarios indicate a cumulative GDP loss of USD 11.8 billion and 11.1 USD billion under slow and fast recovery scenarios, respectively, by December 2020. Our estimates show that Pakistan’s annual GDP (at market prices) will register a decline of 4.6 percent in the year 2020 due to negative effects of the pandemic and sluggish economic recovery. Poverty is expected to stabilize at 27.6 percent and 27.4 percent for the two recovery scenarios by December 2020.